Diagnosis and Surgical Treatment of Idiopathic Primary Sino-Nasal Obstruction in Miniature Horse Breeds: Long-Term Follow-Up of Seven Cases - Vlaminck, Lieven; Pollaris, Elke; Vanderperren, Katrien; Tremaine, W. Henry; Raes, Els (Frontiers in Veterinary Science, 2021)
Idiopathic sino-nasal obstruction resulting in retention of large amounts of liquid in the paranasal sinus compartments was diagnosed in 7 young (2.2 ± 0.7 years) miniature-breed horses based on clinical, endoscopic, radiographic, and CT-scan examinations. The most prevalent clinical signs included decreased or no airflow from the nostril(s) (7/7) and nasal discharge (6/7). The problem presented bilaterally in 6/7 cases. An alternative sino-nasal communication was created through bone flap osteotomy surgery and perforation of the ventromedial floor of the dorsal conchae in all cases, followed by fixation of silicone irrigation tubes/Foley catheters in 6/7 cases to keep the newly created ostium patent. This resulted in long-term resolution of the problem with good cosmetic appearance in all animals following a median period of 19 months. Premature loss of fixed tubes was reported in 3 cases.